Síntese e caracterização de cristais líquidos discóticos derivados da quercetina - Lucca, Étor Gonçalves (2018)
There is a growing demand for new, intelligent materials that have the least impact on the environment. Discotic liquid crystals are therefore well studied due to their capacity of self-organization, presenting greater charge transport than most of the organic materials, allowing their application in photovoltaic cells, unidimensional conductors, transistors and OLED’s. In this work, quercetin was used as a rigid core, aiming to obtain new liquid crystals with potential application in optoelectronic devices. Quercetin is a natural flavonoid found in fruits, vegetables, teas and has been studied in the medicinal field due to its antioxidant, antiallergic, antitumor and antimicrobial properties. Due to its high conjugation it can be modified and applied in several types of optoelectronic devices. In this work six novel molecules derived from quercetin were synthesized through different routes. Three molecules were obtained from the alkylation of quercetin with different benzyl bromides and three other molecules were obtained from the esterification of quercetin with carboxylic acids containing different amounts of carbon chains. After chemical characterization by NMR-1H, FT-IR and mass spectroscopy and thermal characterization by MOLP, DSC, XRD and TGA, the compounds QA8C (alkylated quercetin derivative of 8 chains) and QE10C (esterified quercetin derivative of 10 chains) showed liquid-crystalline properties with hexagonal columnar mesophase from 67 to 100 °C. With all the compounds of the series synthesized, an ideal number between 8 and 10 side chains could be observed, so that there is a liquid-crystalline characteristic.